Leveraging Mobile Augmented Reality Devices for Enabling Specific Human Behaviors in Design and Constructability Review - Suleiman Alsafouri; Steven K. Ayer (Advances in Civil Engineering)
Augmented reality (AR) may support effective design and constructability reviews by providing both the physical exploration benefits of traditional physical mock-ups and also the flexibility benefits of building information models (BIM). Many different types of mobile computing devices can present the same technical AR environment, but it remains unclear how the different properties of the devices impact user behaviors in an architecture, engineering, and construction (AEC) context. This study tasked users with completing the same design review task, using the same technical AR environment but viewed through different commercially available mobile AR devices. Specifically, 32 participants were tasked with collaboratively laying out and reviewing a simple office design using the randomly assigned AR device. Results showed 11 different behaviors were observed and different mobile computers elicited different behaviors. To add further context to the findings, the results were compared to those of a similar, previously published study where users completed a design review with the option to choose one or multiple AR devices. For several types of behaviors, including alternative design formation, navigation of design, and problem solving, no differences were observed between either groups or based on specific AR devices. Conversely, for other behaviors, including explanative, decision making, and discussions with team members, participants did not engage in these behaviors when they could self-select devices, but these behaviors were observed when participants were forced to use a particular device. This suggests that, for some applications, while users may tend to prefer one type of AR interface, they are fully capable of performing the same types of design review tasks with any AR device. The novelty of this work is in demonstrating how the context in which devices are applied impacts the ways in which they are used. This may help future practitioners and researchers to strategically choose to use, or not to use, certain types of devices to elicit specific behaviors.